PEMBERDAYAAN EKONOMI DIGITAL: PELATIHAN TIKTOK AFFILIATE UNTUK IBU PKK DESA KUDIKAN LAMONGAN - Fatichatur Rachmaniyah; Muhammad Hafidh Nasrullah; Fita Velina Sari; Kis’atin Nuroh; Nurul Fadillah (P3M Politeknik Negeri Malang, 2025)
The TikTok Affiliate training program held in Kudikan Village aimed to enhance the digital literacy and skills of PKK housewives in utilizing the platform for marketing and business, thereby creating flexible additional income. Conducted on July 12, 2025, at the village hall by KKN students from Universitas Islam Darul Ulum Lamongan, the training employed a Persuasive-Educative approach in a workshop format, focusing on hands-on practice, discussion, and Q&A. Participants were taught step-by-step methods for creating, managing, and marketing products via TikTok Affiliate. The post-implementation evaluation demonstrated high success: motivation to become an Affiliator reached 100% (17 out of 17 participants) , and technical understanding of the business model increased sharply from 29.4% (pre-survey) to 94.1% (post-evaluation). These results confirm that the hands-on and systematic method was highly effective in transferring technical skills and boosting motivation. Identified challenges included account verification, follower growth, and creating consumer-engaging content. Future recommendations include a follow-up mentorship program and advanced training sessions.